2015
DOI: 10.1038/jcbfm.2014.217
|View full text |Cite
|
Sign up to set email alerts
|

U0126 Attenuates Cerebral Vasoconstriction and Improves Long-Term Neurologic Outcome after Stroke in Female Rats

Abstract: Sex differences are well known in cerebral ischemia and may impact the effect of stroke treatments. In male rats, the MEK1/2 inhibitor U0126 reduces ischemia-induced endothelin type B (ETB) receptor upregulation, infarct size and improves acute neurologic function after experimental stroke. However, responses to this treatment in females and long-term effects on outcome are not known. Initial experiments used in vitro organ culture of cerebral arteries, confirming ERK1/2 activation and increased ETB receptor-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 35 publications
5
41
0
Order By: Relevance
“…One approach is to monitor two to three consecutive reproductive cycles by daily collection of vaginal smears and selecting animals at one or several stages of the reproductive cycle, although this increases the number of animals used. In a study examining a MEK1/2 inhibitor on ischemic stroke outcome, female rats in estrus or diestrus were specifically selected (when estrogen levels are low) and small within-group variations in infarct volume and functional outcome were documented [130]. However, if the intent is to model clinical stroke, the use of reproductively senescent or aged animals is desirable, as stroke outcome is different in young, middle-aged and aged male and female mice and the efficacy of neuroprotective agents differ in the aged brain [71].…”
Section: Studying Sex Differences In Strokementioning
confidence: 99%
“…One approach is to monitor two to three consecutive reproductive cycles by daily collection of vaginal smears and selecting animals at one or several stages of the reproductive cycle, although this increases the number of animals used. In a study examining a MEK1/2 inhibitor on ischemic stroke outcome, female rats in estrus or diestrus were specifically selected (when estrogen levels are low) and small within-group variations in infarct volume and functional outcome were documented [130]. However, if the intent is to model clinical stroke, the use of reproductively senescent or aged animals is desirable, as stroke outcome is different in young, middle-aged and aged male and female mice and the efficacy of neuroprotective agents differ in the aged brain [71].…”
Section: Studying Sex Differences In Strokementioning
confidence: 99%
“…It is demonstrated that U0126 specifically inhibits mitogen‐activated protein kinase kinase (MEK) 1/2 and thus inhibits activation of ERK1/2 both in vitro and in vivo (Edvinsson & Povlsen , Ahnstedt et al . ). We have shown that treatment with the MEK1/2 inhibitor U0126 reduces infarct size after experimental focal ischaemic stroke (Henriksson et al .…”
mentioning
confidence: 97%
“…Recently, we conducted a study in female rats that indicated MEK1/2 inhibition does improve long‐term neurological outcome (Ahnstedt et al . ). However, it is not known whether similar effects occur in male rats.…”
mentioning
confidence: 97%
“…In pig, pERK levels in the retina have been shown to spike immediately after increased intraocular pressure induced ischaemia (Gesslein et al 2010). Phosphorylation of ERK and inhibition of the ERK1/2 pathway by U0126 have previously been demonstrated in rat cerebral vasculature after cerebral ischaemia (Maddahi & Edvinsson 2010;Ahnstedt et al 2015;Povlsen & Edvinsson 2015). We opted for a visual confirmation of pERK manifestation in rat ophthalmic artery as a proof of concept that the pathway is indeed active and potentially involved in the regulation of vasoconstrictive receptors in rat ophthalmic artery.…”
Section: Discussionmentioning
confidence: 99%
“…U0126 does not directly modulate contractility on fresh arteries. Within cerebral ischaemia, it has been suggested that administration of U0126 immediately after ischaemia and up to 24 hr later yields better outcomes both behaviourally and morphologically in rats (Maddahi & Edvinsson 2010;Ahnstedt et al 2015). The role of the MEK/ERK1/2 pathway in retinal ischaemia has been described as a double-edged sword, regulating vasoconstriction as well as promoting M€ uller cell activation and cell survival (Bringmann et al 2006).…”
Section: Discussionmentioning
confidence: 99%